ACE2-binding exposes the SARS-CoV-2 fusion peptide to broadly neutralizing coronavirus antibodies - Low, Jun Siong; Jerak, Josipa; Tortorici, M. Alejandra; McCallum, Matthew; Pinto, Dora; Cassotta, Antonino; Foglierini, Mathilde; Mele, Federico; Abdelnabi, Rana; Weynand, Birgit; Noack, Julia; Montiel-Ruiz, Martin; et al. (Science (American Association for the Advancement of Science), 2022)
The coronavirus spike glycoprotein attaches to host receptors and mediates viral fusion. Using a broad screening approach, we isolated seven monoclonal antibodies (mAbs) that bind to all human-infecting coronavirus spike proteins from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immune donors. These mAbs recognize the fusion peptide and acquire affinity and breadth through somatic mutations. Despite targeting a conserved motif, only some mAbs show broad neutralizing activity in vitro against alpha- and betacoronaviruses, including animal coronaviruses WIV-1 and PDF-2180. Two selected mAbs also neutralize Omicron BA.1 and BA.2 authentic viruses and reduce viral burden and pathology in vivo. Structural and functional analyses showed that the fusion peptide–specific mAbs bound with different modalities to a cryptic epitope hidden in prefusion stabilized spike, which became exposed upon binding of angiotensin-converting enzyme 2 (ACE2) or ACE2-mimicking mAbs. Seven coronaviruses cause human disease, and three have caused serious outbreaks in the past 20 years. The potential for future coronavirus outbreaks in humans and the ongoing resistance of severe acute syndrome coronavirus 2 (SARS-CoV-2) variants to existing antibodies make it important to identify cross-reactive antibodies that can be the basis of therapeutics and can guide vaccine design. Low et al . and Dacon et al . isolated antibodies from convalescent individuals that show broad neutralizing activity against a range of coronaviruses, including Omicron variants of SARS-CoV-2. The antibodies target a conserved region of the viral spike protein known as the fusion peptide and may act by preventing the cell fusion that is required for infection of new host cells. —VV A class of broadly reactive antibodies target a cryptic fusion peptide epitope exposed upon coronavirus spike protein binding to ACE2.